Access improvement in healthcare: a 12-step framework for operational practice - Allen M. Chen (Frontiers in Health Services)
BackgroundAccess improvement is a fundamental component of value-based healthcare as it inherently promotes quality by eliminating chokepoints, redundancies, and inefficiencies which could hinder the provisioning of timely care. The purpose of this review is to present a 12-step framework which offers healthcare organizations a practical, thematic-based foundation for thinking about access improvement.MethodsThis study was designed based on the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) statement. A literature search of prospective peer-reviewed publications was undertaken to identify studies pertaining to healthcare access. Articles published from January 2014 to January 2024 were included. An interpretive synthesis was then presented.ResultsA total of 469 peer-reviewed studies were identified. The most common diseases analyzed were related to general medicine/family practice (N = 75), surgical care (N = 51), health screening (N = 30), mental health (N = 27), cardiovascular disease (N = 17), emergency room/critical care (N = 15), and cancer (N = 7). The remaining 247 studies (53%) did not specifically report on any specialization. The core themes could be broadly categorized into the following: workforce adequacy, patient experience, physical space utilization, template optimization, scheduling efficiency, process standardization, cost transparency, physician engagement, and data analytics. Sixty publications (13%) focused at least in part on equity issues, structural racism, and/or implicit bias; and 25 publications (5%) addressed disparities in education, training, and/or technical literacy. Seventy-three publications (16%) focused either completely or in part on digital health as a means of access improvement.ConclusionBased on this systematic review, a 12-step thematically based framework for approaching access improvement in healthcare was developed.